Quem é filho de Gérson não deve temer a ninguém! Trajetória de uma mãe-da-santo na Umbanda - Silva, Jandson Ferreira da (2009)
The religion, like a form of. To know about and to organize the things of the world, appeared as question for the Anthropology and it has folloied its development since its beginning as science. Like a fact social total, the analysis of the religious field makes possible to glimpse the most varied spheres of the social life, such as: economy, politics, aesthetic, blood relations… I consider here a study of case of a place of fetichism of Umbanda located in the quarter of the Pirambu, Fortaleza. From the narratives - ritual and personal - I’ve folloied the generations of a group that does not remain the same throughout the time. Some elements enter; others (already without use) leave; others still are remeaning, however without a radical change of the cult structure. Admitting itself that all religion is a rearrangement of preexisting beliefs, the Umbanda is only used of these interrituals to reaffirm its condition since the sprouting: a flexible religion and in constant construction.